Layers: Steve Sabella- Selected Works 2006-2014 - Sabella, Steve (Kuwait; Contemporary Art Platform, 2014)
Exhibition catalog. Text: Abed AlKadiri, Malu Halasa.
English
Keywords: N4390-5098 Visual Arts- Exhibitions; Palestine